ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN PADA PENGGUNA GRABFOOD SAAT PANDEMI COVID 19 - Apriliani, Afilda; Nugraheni, Titi; Misdiyono, Misdiyono (Synergy : Jurnal Ilmiah Multidisiplin, 2024)
The research aims to analyze the influence of service quality, promotions and price perceptions on the purchasing decisions of GrabFood users during the Covid 19 pandemic among the people of Jakarta. The research method used is multiple linear regression analysis. Data analysis in this study uses primary data through a questionnaire instrument from 100 respondents who are users of the GrabFood application in Jakarta. The sampling method in this research used a purposive sampling technique. Test and analysis tools using the SPSS program. The research results show that service quality has no effect on purchasing decisions, promotions have an effect on purchasing decisions, price perceptions have an effect on purchasing decisions and together service quality, promotions and prices have an effect on purchasing decisions of GrabFood users in Jakarta.